(untitled) (Journal of Oriental Studies, 2019)
The article deals with the concept of “love” in the myths of ancient Turks. Love in ancient myths is compared with its manifestations and in world mythology. In the history of the Turkic people, love is mentioned. The author tried to distinguish such stories from Greek, Chinese and Turkish myths. In the history of the Turkic people, the concept of love is a significant phenomenon that can be seen from the life philosophical prism. Therefore the concept of love unites practical semantic levels as an object of thinking. Moreover, Tengri, as the supreme deity and Umai An, are represented as the beginning of men and women. Which in mythology are as concerned about love as their creations. This indicates the im- portance of this feeling in the culture of the ancient Turks. Key words: love, concept, thoughts, faith, Umay, Tanir.